Pengaruh Budaya Organisasi dan Motivasi Terhadap Kinerja Karyawan PT. Kawan Lama Sejahtera - Firdausya, Amanatul (Jurnal ATAMA, 2022)
The purpose of this study was to determine the effect of employee organizational culture on employee performance, to determine the effect of motivation on employee performance and to determine the effect of organizational culture and motivation on employee performance at PT. Kawan Lama Sejahtera. This study used a quantitative approach, while the population in this study were all employees of PT. Kawan Lama Sejahtera as many as 32 employees while the sample was saturated so that the sample was taken entirely from the total population with a sample of 32 employees of PT. Kawan Lama Sejahtera. The results of this study obtained results in hypothesis 1 t count > t table (2.433 > 2.037) with a significance level <0.05 so that there is a significant influence between organizational culture on employee performance, in hypothesis 2 t count > t table (4.572 > 2.037) with a level significance <0.05 so that there is a significant influence between motivation on employee performance and in hypothesis 3 the results F count > F table (11.833 > 3.305) with a significance level <0.05 so that there is an influence between organizational culture and motivation on employee performance at PT. Kawan Lama Sejahtera. The conclusion of this study is that both partially and simultaneously have a positive and significant effect.